2018
DOI: 10.1007/s12013-018-0849-2
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor Beta (TFG-β) Concentration Isoforms are Diminished in Acute Coronary Syndrome

Abstract: Acute coronary syndrome (ACS) is the leading cause of death in elderly patients worldwide. Due its participation in apoptosis, fibrosis, and angiogenesis, transforming growth factor-β (TGF-β) isoforms had been categorized as risk factors for cardiovascular diseases. However, due their contradictory activities, a cardioprotective role has been suggested. The aim was to measure the plasma levels of TGF-β1, 2, and 3 proteins in patients with ACS. This was a case-control study including 225 subjects. The three act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“… 54 In the present study, we found that the TGF-β level was reduced and IL-6 level increased in ACS patients compared to CCS and control patients, consistent with the literature. 39 , 55 Meanwhile, we found that TIGIT+Tregs were downregulated in ACS, and an inverse association between IL-6 and TIGIT+Tregs was observed. In contrast, a positive correlation between TGF-β and TIGIT+Tregs was found.…”
Section: Discussionmentioning
confidence: 79%
“… 54 In the present study, we found that the TGF-β level was reduced and IL-6 level increased in ACS patients compared to CCS and control patients, consistent with the literature. 39 , 55 Meanwhile, we found that TIGIT+Tregs were downregulated in ACS, and an inverse association between IL-6 and TIGIT+Tregs was observed. In contrast, a positive correlation between TGF-β and TIGIT+Tregs was found.…”
Section: Discussionmentioning
confidence: 79%